Russian Federation : How Services Contribute to Competitiveness - Saez, Sebastian; van der Marel, Erik (World Bank, Washington, DC, 2016)
Globalization is creating many new trade and growth opportunities, with services trade increasingly becoming an issue for export-oriented economies. Services are important to country trade strategies, because they represent activities in which countries may have a comparative advantage, and they are drivers of competitiveness for the whole economy. This paper uses data from the World Development Indicators, two new databases (the Export in Value-Added database from the Global Trade Analysis Project, and Trade in Services data), and firm-level data. The paper employs a wide range of indicators to analyze the trade competitiveness of the services sector in the Russian Federation. Since service exports are less than would be expected considering Russia's level of development, the study finds that the contribution of services to export diversification could be heightened significantly. The scale of Russian business services exports is relatively low, although exports of traditional services, like transport and travel, are performing well. Despite the relatively minor importance of exports of modern services, the category of other business services has in recent years been growing fast, and business services have strengthened their revealed comparative advantages. Yet Russia still has much potential for expanding trade in modern services. There is also potential to diversify services exports to other markets, such as France, Germany, Japan, and elsewhere in Asia, which today seems underexploited. Finally, although exports of direct services are low, services such as transport, distribution, finance, and other business services are making major contributions to other exports, in particular energy.